Brightside - Marley, Ziggy (Tuff Gong Worldwide, 2026)
Ziggy Marley returns with his first studio album in eight years, delivering an introspective and uplifting collection centered on healing, compassion, and perspective. Recorded at 432Hz, the music blends reggae, rock, funk, and blues with his signature warmth and depth. The album features guest appearances from Trombone Shorty, Sheila E., and Jake Shimabukuro.